Balancing Revenue and Retention: The Impact of VAT Based Digital Taxation on Platform Strategy and Consumer Behavior in Indonesia - Indriasari, Ika; Nurlaela, Lina (Indonesian Scientific Publication, 2025)
The rise of digital services has transformed global consumption patterns and presented challenges for traditional taxation systems. In response, Indonesia implemented a digital VAT policy known as Pajak Pertambahan Nilai Perdagangan Melalui Sistem Elektronik (PPN PMSE), targeting foreign digital service providers. This study examines the pricing impacts of this policy by analyzing the responses of Netflix (2020) and Spotify (2025) to the VAT imposition. Using an event study methodology and price tracking data, we estimate the pass through rate of VAT to consumers and explore associated consumer behavior. The analysis reveals that Netflix’s pricing fully incorporated the 10% VAT in 2020, reflecting a near complete pass through rate. Early reports indicate that Spotify is expected to adjust pricing similarly in response to the 2025 VAT rate update (12% nominal, 11% effective). These findings suggest that VAT burdens are primarily transferred to end users, especially in subscription based digital services. Consumer sensitivity to these price changes varied by income and perceived service value, with digital literacy and price transparency playing moderating roles. Our results support prior empirical research showing inelastic demand in OTT services and underscore the importance of clear tax communication. While inflation and macroeconomic factors complicate price attribution, platform strategies such as loyalty programs and inclusive pricing appear effective in maintaining user retention. The Indonesian case illustrates how VAT frameworks can achieve fiscal objectives without disrupting digital service markets. This study contributes to ongoing debates on digital tax policy by providing empirical insights from a major emerging economy. The findings affirm the administrative feasibility and policy coherence of VAT based digital taxation, offering lessons for other jurisdictions navigating similar reforms.